LOAD BALANCING IN CLOUD COMPUTING - Tyagi, Priyam; Kishor, Amit (International Journal of Computer Sciences and Engineering, 2025)
Cloud Computing is a computing interpretation which provides convenient way to access resources and in which data can be stored on paid basics. It has become a major component of our life. It provides storage of data at minimal cost. Resource allocation plays an important role in Cloud Computing, as it optimize the response time on cloud. Cloud Computing become popular as it provide access on paid basics. Thus, assets allocation is necessary. Load Balancing is one of the methods in Cloud Computing which helps in balancing loads as it increase the throughput and minimize the response time. It distributes loads uniformly on nodules and increase overall performance in the system. The aim of Load balancing is to allocate resources and guarantees user satisfaction. In this paper I explore two of the Cloud computing Algorithms to overcome load balancing in it